1983
DOI: 10.1111/j.1365-2125.1983.tb01521.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the plasma protein binding of theophylline in health.

Abstract: 1 The plasma protein binding of theophylline was determined after addition of ['4C]-theophylline (15 ,g/ml) to plasma from 24 healthy drug-free volunteers and equilibrium dialysis for 2 h at 37°C. 2 The percentage of drug unbound was 60.0% 2.2% (s.d.) with very little variation between individuals. The binding ratio of theophylline was not significantly related to the plasma albumin or a,-acid glycoprotein (AAG) concentrations but was significantly, although weakly, negatively related to the logarithm of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 21 publications
1
15
1
Order By: Relevance
“…Their finding of concentration-dependent protein binding of theophylline between 5-20 mg/l is, however, at variance with our observations (Buss et al, 1983). Other authors have also suggested that theophylline protein binding could fall with increasing drug concentration.…”
contrasting
confidence: 66%
See 1 more Smart Citation
“…Their finding of concentration-dependent protein binding of theophylline between 5-20 mg/l is, however, at variance with our observations (Buss et al, 1983). Other authors have also suggested that theophylline protein binding could fall with increasing drug concentration.…”
contrasting
confidence: 66%
“…Both of these studies used equilibrium dialysis to measure free fraction of theophylline under conditions of controlled temperature (37°C) and pH (7.4) which was not the case with some of the original studies of theophylline plasma protein binding (Buss et al, 1983).…”
mentioning
confidence: 99%
“…The mean plasma protein binding in these patients of 58.2 + 5.09%, is similar in males (57.7 + 5.06%) and females (58.8 + 5.1%). These findings are consistent with those of other authors using ultrafiltration (Antal et al, 1981;Aslaksen et al, 1981;Yurchak & Jusko, 1976;Piafsky etal., 1980;Mangione etal., 1978) but somewhat higher than those obtained by equilibrium dialysis at 37°C (Buss et al, 1983;Brors et al, 1983) showing that theophylline binding is temperature dependent, as well as pH dependent (Vallner et al, 1979). There also appears to be a very weak correlation between age and free fraction (r = 0.411) such that theophylline plasma protein binding decreases with advancing years, as reported for other drugs (Wallace et al, 1976;Patterson et al, 1982).…”
Section: Resultsmentioning
confidence: 88%
“…Tissue:plasma partition coefficients were estimated using in silico tissue composition-based algorithms published by Rodgers et al (2005a,b) and Rodgers and Rowland (2006). Albumin was denoted as the principle binding protein of theophylline in plasma with an average fraction unbound of approximately 0.58 in healthy adults (Buss et al, 1983;Leopold et al, 1985). Human intestinal permeability was estimated for theophylline by scaling from in vitro Caco-2 data (Parrott et al, 2009).…”
Section: Methodsmentioning
confidence: 99%